A Collaborative Anatomy Course for BME Graduate Students: An Institutional Longitudinal Case Study of Multidisciplinary Integration Using Labs and Assignments - Emily L. Bradshaw; Alain J. Kassab; Luigi E. Perotti (Biomedical Engineering Education, 2026)
Purpose Biomedical engineering (BME) is a multidisciplinary field that aspires to improve patient treatment and quality of life by merging expertise across medicine and engineering. Delivery of the appropriate level of human anatomy and physiology is critical to the training of BME students so that their engineering knowledge can be used to understand and solve meaningful medical challenges. To enable this type of training, BME graduate programs may benefit from collaborations with medical education departments as this would allow BME students experiences focused on anatomy, pathology, and clinical imaging. Methods We created a two-semester Biostructures course to introduce BME graduate students to anatomical, physiological, and pathology concepts. To complement lectures, we incorporated gross anatomy laboratory experiences, Anatomage, anatomical structure measurement, computed tomography (CT) imaging, histology and clinical skills sessions, and a research project. We describe the following components: (1) the partnership between medical and engineering education; (2) the development of interdisciplinary experiences and homework incorporating anatomy and engineering concepts; and (3) the course modifications through the past 4 years. Results End-of course student reflections were analyzed to understand BME student perceptions of the interdisciplinary gross anatomy lab experiences and the use of engineering concepts to further their understanding of physiology. The anatomy laboratories were rated very highly and perceived by the students as helpful to further their understanding of how engineering knowledge can be applied to solve medically relevant problems. Similarly, students rated two interdisciplinary homework assignments as both difficult and a good exposure relating their quantitative engineering skills to anatomy and physiology. Conclusions Overall, this case study shows that BME graduate students find the interdisciplinary gross anatomy experiences engaging and perceive them to significantly help in their intended profession.

Responses of Liolaemus lizards to environmental heterogeneity: Linking microhabitat selection and thermal ecology in southern Patagonia - Candela Victorel; Mauro I. Bonavita; Martin C. Castillo; Débora L. Moreno Azocar; María G. Perotti; Félix B. Cruz; Oscar A. Stellatelli (Journal of Thermal Biology, 2026)

Short- and mid-term fire effects on the giant cactus Trichocereus terschekii: drivers of survival and growth - Pedro Jaureguiberry; Nayla L. Aliscioni; Marina A. Lorenzati; Solana B. Perotti; M. Emilia Soto Acosta; Martín Senestrari; Daihana Argibay; Diego E. Gurvich (Journal of Arid Environments, 2026)

Biomedical Engineering Students Report Positive Experiences Learning Anatomy from Human Cadavers - Emily L. Bradshaw; Luigi E. Perotti; Alain Kassab (Biomedical Engineering Education, 2025)

Causes of mortality in wild European hedgehog (Erinaceus europaeus) populations in Italy and Switzerland - I. Prandi; E. Dervas; E. Colombino; L. Bertolotti; M. Cardello; D. Ippolito; M. Perotti; M. Vacchetta; S. Zanet; M. Mauthe Von Degerfeld; G. Quaranta; U. Hetzel; et al. (Journal of Comparative Pathology, 2024)

A lithostratigraphic reappraisal of a Permian-Triassic fluvial succession at Allan Hills (Antarctica) and implications for the terrestrial end-Permian extinction event - Gianluca Cornamusini; Luca Zurli; Giovanni P. Liberato; Valentina Corti; Erik L. Gulbranson; Matteo Perotti; Sonia Sandroni (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

STONE Pietre Egizie: a Free Mobile Application for Promoting the Scientific Research on Ornamental Stones of Museo Egizio of Torino, Italy - D. Valentino; A. Borghi; A. d’Atri; F. Gambino; L. Martire; L. Perotti; G. Vaggelli (Geoheritage, 2020)

Following the Tracks of Charlemagne in the Cottian Alps. The Cultural and Geological Heritage of the Franks Trail (Susa Valley, Piemonte, NW Italy) - E. Giordano; M. Giardino; L. Perotti; L. Ghiraldi; M. Palomba (Geoheritage, 2016)

Assessment of cryopreserved donor skin viability: the experience of the regional tissue bank of Siena - E. Pianigiani; L. Tognetti; F. Ierardi; G. Mariotti; P. Rubegni; G. Cevenini; R. Perotti; M. Fimiani (Cell and Tissue Banking, 2016)

GIS and geomatics for disaster management and emergency relief: a proactive response to natural hazards - M. Giardino; L. Perotti; M. Lanfranco; G. Perrone (Applied Geomatics, 2012)

Potential distribution of Batrachochytrium dendrobatidis in Argentina: implications in amphibian conservation - R. Ghirardi; M. G. Perotti; M. M. Steciow; M. L. Arellano; G. S. Natale (Hydrobiologia, 2011)